A highly selective HBT-based "turn-on" fluorescent probe for hydrazine detection and its application. Issue 26 (28th June 2017) - Chen, Zhen; Zhong, Xinxin; Qu, Wangbo; Shi, Ting; Liu, Heng; He, Hanping; Zhang, Xiuhua; Wang, Shengfu
Graphical abstract: A novel turn-on fluorescent probe HBTM for N2 H4 detection based on ESIPT and ICT mechanism was designed. Highlights: Turn-on fluorescent probe for N2 H4 detection was developed based on ESIPT and ICT. The linear range of probe HBTM for N2 H4 is 0–140 μM. The probe can be applied for N2 H4 detection on paper strips and in living cells. Abstract: As one of the important industrial chemicals, hydrazine (N2 H4 ) can be inhaled through the skin, leading to many serious health issues. In this paper, we constructed a novel turn-on fluorescent probe HBTM for N2 H4 detection based on ESIPT and ICT mechanism by incorporating the methyl dicyanvinyl group to 2-(2′-hydroxylphenyl) benzothiazole (HBT) fluorophore. The probe showed the following advantages: high sensitivity with detection limit of 2.9 × 10 −7  M, high selectivity over other related interfering species, wide linear range of 0–140 μM and pH value adaptation. Moreover, the probe could detect N2 H4 on paper strips and image N2 H4 in living cells.